Five Cyanophora (Cyanophorales, Glaucophyta) species delineated based on morphological and molecular data. Issue 6 (28th October 2014) - Takahashi, Toshiyuki; Sato, Mayuko; Toyooka, Kiminori; Matsuzaki, Ryo; Kawafune, Kaoru; Kawamura, Mai; Okuda, Kazuo; Nozaki, Hisayoshi; Wetherbee, R.
<x xml:space="preserve">Abstract</x> Cyanophora is an important glaucophyte genus of unicellular biflagellates that may have retained ancestral features of photosynthetic eukaryotes. The nuclear genome of Cyanophora was recently sequenced, but taxonomic studies of more than two strains are lacking for this genus. Furthermore, no study has used molecular methods to taxonomically delineate Cyanophora species. Here, we delimited the species of Cyanophora using light and electron microscopy, combined with molecular data from several globally distributed strains, including one newly established. Using a light microscope, we identified two distinct morphological groups: one with ovoid to ellipsoidal vegetative cells and another with dorsoventrally flattened or broad, bean‐shaped vegetative cells containing duplicated plastids. Our light and scanning electron microscopy clearly distinguished three species with ovoid to ellipsoidal cells (C. paradoxa Korshikov, C. cuspidata Tos.Takah. & Nozaki sp. nov., and C. kugrensii Tos.Takah. & Nozaki sp. nov.) and two species with broad, bean‐shaped cells (C. biloba Kugrens, B.L.Clay, C.J.Mey. & R.E.Lee and C. sudae Tos.Takah. & Nozaki sp. nov.) based on differences in cell shape and surface ornamentations of the vegetative cells under the field‐emission scanning electron microscope. Molecular phylogenetic analyses of P700 chl a apoprotein A2 (psaB) genes and internal transcribed spacer (ITS) regions of nuclear ribosomal DNA (rDNA), as well as a comparison of secondary structures of nuclear rDNA ITS‐2 and genetic distances of psaB genes, supported the delineation of five morphological species of Cyanophora.